Gli scritti (1928-1944) - Dietrich Bonhoeffer; Eberhard Bethge; Maria Cristina Laurenzi (Brescia Queriniana, 1979)
Maria Cristina Laurenzi (ed. it.)
Edizioni San Paolo srl - Piazza Soncino, 5 - 20092 CINISELLO BALSAMO (MI) (non commercial uses only) ® Copyright 2018